(3TQM eNJUQ GdeRfis - (3WGgQ Hf YHO Gddg Hf WGgQ GdWHQj, CHh GdWqjH , (B450 (3g` s; (3GdeRfj , ESeGYjd Hf jMji Hf ESeGYjd, CHh EHQGgje,J (B264 (3g` s
(3ChdgG (B:s
(3HGH Gdhba ef cJGH GdEjdGA s
(3BNQgG (B:s
(3HGH Yah GdeMfi Ydjg YeOkG Ke jehJ hZjQ Pdc s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B299s
Keywords: (3Gdabg GdTGaYjs